Performance of heat pumps using pure and mixed refrigerants with maldistribution effects in plate heat exchanger evaporators. (August 2019) - Mancini, Roberta; Zühlsdorf, Benjamin; Aute, Vikrant; Markussen, Wiebke Brix; Elmegaard, Brian
Highlights: A coupled plate heat exchanger - heat pump design and off-design model is presented. Effect of end plates and liquid/vapour maldistribution are considered in evaporators. Maldistribution entails a degradation of both evaporator and cycle performance. Refrigerants sensitivity to maldistribution is related to sensitivity to pressure drop. Maldistribution may impact the levelized specific cost of heat of the heat pump. Abstract: This paper presents a combined plate heat exchanger (PHE) - heat pump simulation framework for the evaluation of flow maldistribution in PHE evaporators and its effect on the cycle thermodynamic and economic performance. A case study of heat pump integration for waste heat recovery purposes in data centres was chosen to demonstrate the utilization of the simulation tool. The analyses were made for the pure fluids butane and propane, and for the zeotropic mixtures propylene/butane at (0.5, 0.5) mass composition and CO2 /dimethyl ether (DME) (0.2, 0.8) as refrigerants. Both liquid/vapour maldistribution and the effect of end plates were considered in the heat exchanger models. Results show that butane is most sensitive to maldistribution, with a maximum Coefficient of Performance (COP) reduction of 5.9%, while propane experiences the lowest reduction of 2.5%. The different sensitivity of the working fluids to maldistribution was found to be related to the evaporator design, refrigerant pressure drop, and fluid properties. Last, the results of the economic analysis show that a higher specific cost of heat is obtained when considering maldistribution effects.